Frequency regulation in power systems that integrate wind energy sources through a pi controller and inertial emulation - Gómez Molina, Nelson; Rivera Rodríguez, Sergio Raúl (Ingeniería Solidaria, 2017)
Introduction: This article derives from the research “Multilevel Control for Microgrids Dispatch Considering Stability Issues through mpc -based Frequency Regulation” conducted at the Universidad Nacional de Colombia during 2016 and the first half of 2017. It presents the study and analysis of a frequency regulation control scheme implemented in a power system that integrates renewable energy sources (res). The objective is to improve the reliability and stability of the grid against typical disturbances of renewable energies. Methodology: Initially, the dynamic response of the power system to sudden disturbances and continuous change was simulated to observe frequency deviations. The control block was also implemented in the additional power loop to emulate inertia and, thus, slow down the response of the system. Subsequently, the control parameters were optimized through heuristic optimization algorithms to minimize the frequency signal error. Results: Using the heuristic optimization of proportional integral (pi) control parameters, it was verified that there is a reduction of more than 79 % in the maximum error of frequency deviation in relation to the open loop response, and more than 43 % with respect to pi control with referential gains. Conclusion: In implementing the additional power loop with pi control, a decrease in the frequency deviation error was found in relation to the open loop simulations, due to the additional power loop.